Corak dan Metode Interpretasi Aisyah Abdurrahman Bint Al-SyÃ¢thiâ€™ - Wahyuddin Wahyuddin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2011)
This article examines the method of interpretation of Bint al-sya-i by studying his book Tafsir al-Tafsir al-BayÃ¢niy li al-Qur'an al-Karim. It has been found that the method applied by al-sya-i' was patterned literature i.e. literary exegesis which is designed to be inter-interpretation of the Quranic text which methodologically, can be considered modern. The method used a thematic approach (maudu'i) in interpreting the Koran and stressed the need for interpretation of philology, based on the chronological text and the use of Arabic semantics. This thematic approach was a response to the classical method of interpretation of the Qur'an by contemporary experts. It is then applied by al-Syathi in his commentary that contains fourteen chapters started Makkiyah entitled â€œal-Tafsi r li al-Bayan al-Qur'an al-Karim.â€